تدابير تيسير التجارة و أثرها في التنمية الاقتصادية: دراسة قياسية لمجموعة من الاقتصادات النامية للفترة 2012 2018. - خليفة خالدي (university Of Eloued جامعة الوادي, 2020)
استهدفت هذه الدراسة قياس وتحليل أثر تدابير تيسير التجارة المتمثلة في مؤشر ربط الشحن البحري، مؤشر جودة البنية التحتية للميناء، مؤشر عبء الإجراءات الجمركية، مؤشر حركة الحاويات في الميناء، في التنمية الاقتصادية معبرا عنها بكل من إنتاجية الفرد العامل، معدل العمالة، ومؤشر التنمية البشرية، لعينة تتكون من 24 دولة نامية من البلدان متوسطة الدخل الشريحة الدنيا) حسب تصنيف البنك الدولي، وذلك خلال الفترة الزمنية 2007-2019 لتحقيق ذلك استخدمت الدراسة منهج بيانات البائل بواسطة تطبيق ثلاثة نماذج قياسية هي نموذج الانحدار المجمع، نموذج الانحدار الثابت، ونموذج الآثار العشوائية. أسهمت الدراسة بما يلي: (1) اقترحت تعريفا جديدا التدابير تيسير التجارة (2) أضافت لبنة تحليلية يعتقد أنه لم يتم التطرق إليها من قبل (3) طبقت نظرة شمولية أثناء البحث التجريبي في التعبير عن مستويات التنمية الاقتصادية. توصلت الدراسة إلى ثلاث نتائج رئيسية (1) تباينت طبيعة تأثير تيسير التجارة في النمو الاقتصادي (2) يؤثر تيسير التجارة سلبا على معدلات العمالة (3) يسهم تيسير التجارة في تحسين أداء مؤشر التنمية البشرية. من أهم التوصيات التي تقدمت بها الدراسة (1) أن تستثمر الحكومات في موضوع تيسير. التجارة خاصة من خلال تخفيف الأعباء الجمركية، وإيلاء الموانئ اهتماما متزايدا (2) ينبغى على المؤسسات الدولية ذات الشأن أن تتبنى تعريفا موحدا لتيسير التجارة (3) التفكير في تطوير نموذج تجاري كفيل بأن يضمن التكاليف الناشئة عن سلاسل الإمداد العالمية. This study aimed to measure and analyze the impact of trade facilitation measures represented in Liner Shipping Connectivity Index, Quality of Port Infrastructure Index, Burden of customs procedures index, and Container port traffic index, on economic development, expressed in terms of the productivity of the working individual, the employment rate, and the human development index, for a sample of 24 developing countries from middle-income countries (the lowest segment) according to the World Bank classification, during the 2007-2019 period. To achieve this, the study used the panel data approach by applying three standard models: The Pooled Regression Model (PRM), the Fixed Effects Model (FRM), and the Random Effects Model (RRM). The study contributed the following: (1) It proposed a new definition of trade facilitation measures. (4) It added an analytical brick that is thought to have not been touched upon before. (3) A holistic view was applied during the empirical research in expressing the levels of economic development. The study reached three main results: (1) The nature of the effect of trade facilitation on economic growth has varied. (2) Trade facilitation negatively affects employment rates. (3) Trade facilitation contributes to improving the performance of the Human Development Index. Among the most important recommendations made by the study: (1) That governments invest in the issue of facilitating trade, especially by reducing customs burdens and giving ports increasing attention. (2) Relevant international institutions should adopt a united definition of trade facilitation. (3) Thinking about developing a commercial model that would include costs arising from global supply chains.
دراسة قياسية لمجموعة من الاقتصادات النامية للفترة 2012 2018
مداخلة
Keywords: تدابير تيسير التجارة; التنمية الاقتصادية; الدول النامية; مؤشرات التنمية; مؤشرات تيسير التجارة